Evaluation of Current Community Pharmacist Practice in Saudi Arabia-A Cross-Sectional Study from Pharmacists' Perspective (Part II) - Mohammad Alhazmi; Abdulmajeed Bajuayfir; Ejaz Cheema; Mahmoud Elrggal; Majid Ali (MDPI AG, 2022)
This study aimed to evaluate the current practice of community pharmacists from patients' and pharmacists' perspectives in Saudi Arabia. This paper presents the pharmacist's perspective. A cross-sectional self-administered online survey was designed to collect responses from community pharmacists in Saudi Arabia from February to April 2021. The questionnaire consisted of several statements related to best practice in community pharmacy. Pharmacists' responses to each statement were scored using a 5-point Likert scale. Higher scores represented a greater extent to which they adhered to best practice in the community pharmacy setting and vice versa. Data of 164 participants were included in the analysis. The minimum median score was related to the statement: Pharmacist explains the main side effects. The maximum median score was related to the statement: Pharmacist explains dosage regimen. Pharmacists aged 30 years or above and non-Saudi pharmacists had significantly higher median scores compared with pharmacists less than 30 years of age (p = 0.016) and Saudi pharmacists, respectively (p = 0.001). A gap between best practice and current practice of community pharmacists was observed. Policymakers can utilize these findings to provide targeted professional development opportunities for the practicing community pharmacists in order to improve the overall service and care for patients.